Development Strategies of Muslim’s MSMEs at Banyoksah Village Sampang Madura Island: Analysis of IFAS and EFAS Matrix - Islamiati Hidayah; Sayekti Indah Kusumawardhany (ITB AAS INDONESIA Surakarta, 2023)
This study is aimed to find out how the Honey Pumpkin business development strategy is carried out by Honey Pumpkin Farmers in Banyusokah Village, Sampang Regency based on EFAS and IFAS Matrix. The method employed in this study is descriptive qualitative which is aims to describe, describe, record, and analyze existing and current conditions. The result of the study showed that Honey Pumpkin business in Banyoksah Village of Sampang Regency is able to implement the growth oriented strategy for developing its business. The suggested strategies are firstly, to distribute the products in the store at Sampang Regency and utilizing social media such as IG, whatsApp and so on for marketing. Secondly, diverging the processed product from honey pumpkin and turning customer into reseller. Thirdly, replacement of production technology used with more sophisticated and modern to increase the production effectively and efficiently. Lastly, opening several branch of store that owned by the company.